2002
DOI: 10.1520/jfs15471j
|View full text |Cite
|
Sign up to set email alerts
|

D1S80 Polymorphism in Istanbul (Turkey)

Abstract: Blood samples were obtained from 78 randomly selected, healthy, unrelated individuals from both sexes and were examined in order to estimate the allele and genotype frequencies of D1S80 locus. DNA was extracted using Chelex 100 extraction method (1). The amplification was carried out according to the instructions of AmpliFLP D1S80 PCR amplification kit (2). The PCR products were analyzed using a vertical denaturating polyacrylamide gel electrophoresis. The gels were silver stained. The statistical analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Mahdieh et al (2005) showed that alleles 23 and 18 are most common in the Iranian population. We did not observe allele 23 in this study, but it was observed at a frequency of 0.007 by Akgunes et al (2002) and 0.009 by Ç akir et al (2001). Sachdeva et al (2004) showed higher frequencies of allele 31 in Thoti and Kolam populations (9-14%) than in other Indian populations.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Mahdieh et al (2005) showed that alleles 23 and 18 are most common in the Iranian population. We did not observe allele 23 in this study, but it was observed at a frequency of 0.007 by Akgunes et al (2002) and 0.009 by Ç akir et al (2001). Sachdeva et al (2004) showed higher frequencies of allele 31 in Thoti and Kolam populations (9-14%) than in other Indian populations.…”
Section: Discussioncontrasting
confidence: 70%
“…Some investigations have studied the frequency of D1S80 alleles in the Turkish population; for example, Attila et al (2004) investigated this locus for prenatal diagnosis. Ç akir et al (2001) and Akgunes et al (2002) investigated D1S80 polymorphisms in the Turkish population using agarose and polyacrylamide gel. The most common alleles found were allele 24 and allele 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations